Moral Agency as Cognitive Agency: Recovering Kant’s Conception of Virtue - Tizzard, Jessica (Con-Textos Kantianos. International Journal of Philosophy, 2020)
Review of: Merritt, M., Kant on Reflection and Virtue, Cambridge, Cambridge University Press, 2018, 219 pp. ISBN 978-1-108-42471-4.